EARNING MANAGEMENT IN MANUFACTURING COMPANIES IS INFLUENCED BY COMPANY CHARACTERISTICS AND AUDIT ELEMENTS - Khairani, Munisha; Siahaan, Magda (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study seeks empirical evidence regarding the effect of growth opportunities, leverage, fixed asset turnover, profitability, company size, company age, audit quality, audit independence, and audit committee on earnings management. This study uses the reporting of manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2018. The research sample consisted of 309 data, which were selected as the final sample using purposive sampling. This study uses multiple regression analysis with the SPSS program to test the relationship between independent and dependent variables. The results of this study indicate that the variables of growth opportunity, profitability, and audit quality affect earnings management. While the variables of leverage, fixed asset turnover, company size, company age, audit independence, and audit committee do not affect earnings management.